Brucellosis as an aetiology of septic arthritis. (January 2014) - Hasanoglu, Imran; Guven, Tumer; Maras, Yuksel; Guner, Rahmet; Tasyaran, Mehmet Akin; Acikgoz, Ziya Cibali
Brucellosis is a zoonotic disease caused by a Gram-negative coccobacillus from the Brucella genus. The disease has a broad spectrum of clinical manifestations. The musculoskeletal system involvement is frequent and, rarely, arthritis can be the only clinical feature of the disease. We report a case of monoarthritis caused by Brucella melitensis .